Effects of Perceived Trust and Perceived Price on Customers’ Intention to Buy in Online Store in Indonesia - Setiawan, Ricky; Achyar, Adrian (ASEAN Marketing Journal, 2021)
Price and trust are important factors that influence customer purchasing decision in online shopping. However, the synergy of these two factors in customer intention to buy still needs to get higher attention. This paper examines the relative influence of perceived trust and perceived price on customers intention to buy, both for customers who have bought item from the store (repeat customers) and who have not (potential customers), and examines whether a difference exists on the strength of influence of price and trust to purchase intention in those groups. Data are analyzed with the multiple group analysis structural equation modeling, comparing the repeat customers and potential customers. The results of this paper reveal that there is no significant difference of effect between perceived trust and perceived price on intention to buy between potential and repeat customers and that perceived trust exerts a stronger effect than perceived price on purchase intentions for both potential and repeat customers of an online vendor. This paper also reveals that while perceived trust exerts a positive influence, perceived price exerts a negative influence on both perceived value and intention to buy.